Penerapan Kurikulum Merdeka Melalui Metode Diskusi Kelompok Untuk Meningkatkan Hasil Belajar IPS Di SMP Negeri 2 Tondano - Erric Kondoy (PT. Citra Media Publishing, 2025)
A significant change in the field of education is marked by the shift from the 2013 Curriculum to the Merdeka Belajar (Independent Learning) Curriculum. At SMP Negeri 2 Tondano, student engagement in Social Studies (IPS) remains relatively low, as evidenced by minimal active participation and low learning motivation. Observations indicate that students tend to be passive and lack focus during the learning process.This study employs a Classroom Action Research (CAR) approach involving eighth-grade students. The findings reveal that the use of appropriate teaching methods, such as group discussion, can enhance students’ learning outcomes and foster positive collaboration among group members during the learning activities.